Kompetensi Manajerial Kepala Madrasah dalam Mengembangkan Kinerja Tenaga Pendidik dan Tenaga Kependidikan - Imron Imron; Purwanto Purwanto; Yusuf Rohmadi (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine the managerial competence of madrasah principals in developing the performance of teachers and education personnel (management study of the principal of Madrasah Aliyah Negeri 1 Pati in Pati Regency). This research was conducted on the implementation of pedagogic competence development at Madrasah Aliyah Negeri 1 Pati which was carried out by the head of madrasah to develop the performance of teaching staff and education personnel. The methodology in this study uses a qualitative approach. Data collection techniques in this study are by observation, interviews and documentation. The method used to check the validity of the data is the triangulation method. Data analysis in this study used qualitative analysis. The results showed that the Principal of Madrasah Aliyah Negeri 1 Pati management of pedagogic competence development at Madrasah Aliyah Negeri 1 Pati included: a) Planning for the head of the madrasah in developing the competence of teachers and education personnel at Madrasah Aliyah Negeri 1 Pati by preparing a work program that was initiated. by deliberation with the teaching staff and education staff in accordance with the regulations set by the government. b) The organizing that was carried out by the Head of Madrasah Aliyah Negeri 1 Pati was to realize the school development policy, especially the development of the competence of teachers and education staff in forming a work team for the quality of decision making. c) the implementation of the Principal of Madrasah Aliyah Negeri 1 Pati, where teaching staff and education personnel realize several main aspects in the program of competency development for teaching staff and education personnel, by disseminating the implementation of competency development for teachers and education personnel, d) Supervision of the Head of Madrasah Aliyah Negeri 1 Pati realized all the activities that were attended by educators and education staff in developing the competencies they mastered.